NILAI-NILAI PENDIDIKAN AKHLAK DALAM NOVEL “NEGERI 5 MENARA” KARYA AHMAD FUADI - Naili Nur Fadzilah (Tarbiya Islamica, 2015)
This research was conducted because of the uniqueness found in the novel Negeri 5 Menara by Ahmad Fuadi. Among them is that this novel is able to provide inspiration and motivation for its readers, because in this novel it is presented in light and easy-to-understand language and is full of moral education values. based on some of these uniqueness, researchers are interested in making the novel Negeri 5 Menara as an object of research with the title "The Values ​​of Moral Education in the Novel Negeri 5 Menara by Ahmad Fuadi". This type of research is library research using a qualitative approach. The data analysis technique used in this research is content analysis, which is drawing conclusions through efforts to find the message contained in the novel Negeri 5 Menara. Based on the data analysis carried out, it can be concluded as follows: 1) The value of moral education towards Allah SWT, is grouped into: faith, prayer, sincerity, gratitude, tawakal, and amar ma'ruf nahi munkar. 2) The value of moral education towards oneself, grouped into: patient, fulfilling the mandate, honest, frugal, disciplined,. 3) The value of moral education towards fellow human beings, are grouped into: birrul walidain, brotherhood, help, and say and answer greetings.